Characterisation of aseptic sterilisation processes using an electronic nose. (29th April 2013) - Reisert, Steffen; Geissler, Hanno; Flörke, Rudolf; Weiler, Christian; Wagner, Patrick; Schöning, Michael J.
The present work describes the development of a multi–sensor system for the evaluation of aseptic sterilisation processes employing hydrogen peroxide vapour by means of an electronic nose. Microbiological count reduction tests with Bacillus atrophaeus spores have been carried out in order to characterise influencing factors of the sterilisation by hydrogen peroxide vapour, namely the hydrogen peroxide concentration, humidity, gas temperature and gas flow. In parallel, three different types of gas sensors have been investigated on sensitivity towards the same parameters. A correlation between the results of the microbiological tests and the response of the gas sensors is drawn.